Energy Scenario of Three Wheeler Electric and Gasoline Vehicle in Hetauda - Uprety, Sabina; Sapkota, Ram Chandra (Journal of Advanced College of Engineering and Management, 2021)
The global shifting away from petroleum fuels and towards more renewable energy sources has resulted in a significant progress in favor of vehicle electrification. The uptake of electric vehicle in the existing fleet of vehicles has positive impacts in the reduction of emissions and reduces the carbon footprints by moving in to greener transport. Nepal is a hydropower resource rich developing country; it can use its clean source of hydroelectricity for public transport electrification. Use of hydroelectricity for transport electrification can help to reduce the dependence on petroleum fuels with significant environmental benefits. This study aims to analyse energy scenarios of Hetauda through primary data survey of 4086 three wheeler as 1874 and 2212 as gasoline and electric respectively. Three scenarios are considered business-as-usual (BAU), ETRM 100 (100% electric tempo replacement)and ETRM 75 (75% electric tempo replacement). Energy demand of Hetauda is 230.4TJ and will be increased to 333.5TJ for the accounting year 2018 and 2035 respectively.